From principles to virtues : a critical analysis of the principles of biomedical ethics, with special reference to end-of-life decisions - Van Zyl, Liezl L (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1997.